Clonidine and dexmedetomidine as adjuvant to ropivacaine for supraclavicular brachial plexus block during upper limb surgery: A comparative study - Sangita Mandal; Sanjay Maitra; Abhijit Mukherjee; Mandal, Mohanchandra (Asian Journal of Medical Sciences, 2022)
Background: Various adjuvants are added to local anesthetics to increase the duration of block during supraclavicular brachial plexus (SCBP) block. Dexmedetomidine, a newer and potent alpha2 receptor agonist, has 10 times higher selectivity than clonidine. Many studies have already evaluated the efficacy of clonidine and dexmedetomidine as perineural adjuvants and have reported wide variations in the prolongation of post-operative analgesia. Some studies have reported the absence of adjuvant’s effect while a few have not focused all the facets of block characteristics. Aims and Objectives: The aim of the study was to compare the efficacy of clonidine and dexmedetomidine as adjuvant to ropivacaine during SCBP block for the upper limb surgeries, in terms of duration of post-operative analgesia (Primary outcome). The onset and duration of sensory and motor block, and adverse effects, if any, were observed. Materials and Methods: Ninety patients, aged between 40 and 60 years of either sex, undergoing upper limb surgery, were randomly allocated in to three groups to receive either 30 ml of 0.5% ropivacaine and 2 ml saline (Group R, n=30) or 30 ml 0.5% ropivacaine plus clonidine (1 mcg/kg) plus saline to make a total volume 32 ml (Group C, n=30), or 30 ml 0.5% ropivacaine and dexmedetomidine (1 mcg/kg) plus saline to make a total volume 32 ml (Group D, n=30). The duration of post-operative analgesia, other block characteristics, and adverse events, if any, was assessed. Results: Mean duration of post-operative analgesia was found to be considerably higher in dexmedetomidine group compared with clonidine group and ropivacaine alone group (664.13 vs. 551.77 vs. 465.47, respectively, P<0.001). The duration of sensory and motor block was considerably longer in dexmedetomidine group compared with clonidine and control group. Adverse events were comparable among the three groups. Conclusion: Dexmedetomidine appears to be a better alternative to clonidine as adjuvant in terms of prolonged post-operative analgesia and comparable adverse events.